ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK DI INDONESIA YANG DIMODERASI OLEH UKURAN - Fahru Rachman; Muslim, Ahmad; Widiastuti, Maria C. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
ABSTRACT   This study aims to analyze the effect of financial ratios consisting of Debt to Equity Ratio (DER), Operating Cost to Operating Income (BOPO), Non Performing Loan (NPL), and Capital Adequacy Ratio (CAR) on profitability (ROA) in the banking industry in Indonesia, with bank size as a moderating variable. This study uses quantitative methods with panel data regression analysis. The data used came from the financial statements of 36 commercial banks listed on the Indonesia Stock Exchange for the period 2018-2021. Based on the test results, it was found that BOPO had a negative effect, NPL and CAR had a positive effect on bank profitability. Meanwhile, DER has no significant effect on profitability. In addition, bank size has proven to moderate the relationship between BOPO, NPL, CAR and bank profitability. The results of this study imply that bank management needs to manage financial ratios such as BOPO, NPL, and CAR optimally to increase profitability, taking into account bank size.